IDENTIFIKASI KANDUNGAN LOGAM BERAT PADA PRODUK TEMPE DI INDUSTRI RUMAH TANGGA DESA KALORAN, KECAMATAN NGRONGGOT, KABUPATEN NGANJUK - Awalia Azizah Widyastuti; Imam Thohari; Pratiwi Hermiyanti (Gema Lingkungan Kesehatan, 2022)
Food products produced and distributed in Indonesia must meet food safety requirements and the maximum threshold for contamination of heavy metals in food. It is necessary to pay attention so as to produce food products that are safe and feasible to be consumed. Household Industry that is often found one of them is soybean tempeh. Aspects of hygiene and sanitation in production activities should be considered because it can allow the contamination of heavy metals that enter the tempeh products through the production process and equipment used. The purpose of the study was to identify heavy metal contamination in tempeh products in kaloran village household industry in Ngronggot subdistrict of Nganjuk regency in 2021. This type of research is descriptive with a cross sectional approach. Using purpusive sampling method with the reason in the household industry has given permission to conduct research and according to the criteria of research conducted, namely the results of tempeh products packaged using plastic. Variables studied: equipment, packaging and labels, as well as soybean tempeh products to be inspected heavy metals Cd, and Pb. Data collection conducted observations, interviews and laboratory examinations. The results showed that the equipment used in production is not eligible, namely 75% equipment material, 50% layout and no supervision. 100% packaging selection using plastic packaging. The contamination of heavy metals cadmium (Cd) and lead (Pb) in tempeh is still below the threshold (SNI). The conclusion of the results of the study shows that the content of heavy metals in the household industry tempeh in the category of eligible. However, it is advisable for industry owners to pay attention to the cleanliness of equipment and the selection of safe packaging for food.